REKONSTRUKSI KEWENANGAN ASAL-USUL ATAS KELEMBAGAAN, PENGISIAN JABATAN, DAN MASA JABATAN KEPALA DESA ADAT - Natanel Lainsamputty; Agus Sudaryanto (Veritas et Justitia, 2025)
This study examines the normative ambiguity in Article 109 of the Village Law, which stipulates that the institutional structure, mechanisms for filling positions, and terms of office of customary (adat) village heads must be determined based on customary law, while at the same time requiring these matters to be stipulated in Provincial Regional Regulations. This formulation creates a dualism of authority between the rights of origin of customary (adat) peoples and the regulatory authority of local governments. Using a normative legal approach through the analysis of laws and regulations, academic literature, and regional regulatory practices, this study finds that the ambiguity of Article 109 has encouraged the emergence of Regional Regulations that are both regulative and interventionist in nature. Local governments not only recognize but also reorganize customary arrangements in detail, including the uniformity of adat institutional structures, the regulation of appointment mechanisms, the determination of genealogical requirements, and the establishment of terms of office for adat village heads. This research proposes a reconstruction of Article 109 by emphasizing that Regional Regulations should function declaratively, namely, by recognizing adat mechanisms rather than re-regulating them. Through this reconstruction model, original authority over institutional structures, appointment mechanisms, and terms of office of adat leaders can be restored as the full domain of adat law communities, thereby enabling state–adat relations to operate proportionally within the framework of Indonesian legal pluralism.